The Hidden Dimension of the Protection Granted as a Result of Filing a Complaint with an Administrative Court (Reflections on the Act of Withdrawal of Countersignature by the Prime Minister - Zbigniew Kmieciak (Krytyka Prawa)
Following a complaint to an administrative court by two judges, the Prime Minister used the self-revision procedure and revoked his countersignature of the Presi-dent’s official act. This is a true precedent in the history of Polish constitutionalism. Yet, the permissibility of judicial review of presidential acts performed in individual cases should not give rise to any doubts. This is because such acts are subject to the general control regime set forth in the Act of 30 August 2002 – Law on Proceed-ings before Administrative Courts. What we can learn from other judicial systems indicates that the acts of central executive authorities are not, with some exceptions, exempt from such supervision. An analysis of the judicial decisions of, for instance, the Supreme Administrative Court of the Czech Republic, which recognises its jurisdiction over appointments of judges serves as a convincing example.